2012
DOI: 10.5402/2012/208760
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Additive Manufacturing

Abstract: Additive manufacturing processes take the information from a computer-aided design (CAD) file that is later converted to a stereolithography (STL) file. In this process, the drawing made in the CAD software is approximated by triangles and sliced containing the information of each layer that is going to be printed. There is a discussion of the relevant additive manufacturing processes and their applications. The aerospace industry employs them because of the possibility of manufacturing lighter structures to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
897
1
36

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,751 publications
(1,015 citation statements)
references
References 44 publications
(73 reference statements)
1
897
1
36
Order By: Relevance
“…[11][12][13][14][15] In addition, the growth restriction factor is equivalent to the rate of development of constitutional undercooling (DT c ) relative to the rate of development of solid (f s ). [16] Recent work includes the work of Tamirisakandala et al who reported the effect of boron on the grain refinement of as-cast Ti-6Al-4V and Ti-6242 [17] and Bermingham et al who studied the same effect for as-cast commercially pure titanium.…”
Section: The High Level Of Interest In Additive Manufacturingmentioning
confidence: 99%
“…[11][12][13][14][15] In addition, the growth restriction factor is equivalent to the rate of development of constitutional undercooling (DT c ) relative to the rate of development of solid (f s ). [16] Recent work includes the work of Tamirisakandala et al who reported the effect of boron on the grain refinement of as-cast Ti-6Al-4V and Ti-6242 [17] and Bermingham et al who studied the same effect for as-cast commercially pure titanium.…”
Section: The High Level Of Interest In Additive Manufacturingmentioning
confidence: 99%
“…This brings cost reduction for small quantities [2] and decreases man-hours in traditional methods. Additive manufacturing technologies enable manufacturing complex parts containing cavities [3]. The 3D printing technology is used in the aerospace industry to make lightweight parts such as the wing with lattice structure [4].…”
Section: Technologymentioning
confidence: 99%
“…According to Literatures, the two main parameters controlling the process of the 3D printing are the printing machine, and the printing ink, which accordingly could determine what kind of product the process could produce [4]. However, for construction purposes, there were 3 main categories that all the trials will fall under: Contour Crafting Method, D-Shape method, and Concrete Printing Method [5].…”
Section: Introductionmentioning
confidence: 99%